1992
DOI: 10.1007/bf00193880
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional particle imaging with a single camera

Abstract: A new approach to the instantaneous three-dimensional mapping of flow fields is introduced. A single camera system uses defocusing in conjunction with a mask (three pin holes) embedded in the camera lens to decode three-dimensional point sources of light (i.e., illuminated particles) on a single image. The sizes and locations of the particle image patterns on the image plane relate directly to the three-dimensional positions of the individual particles. Using sequential images, particles may be tracked in spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
140
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(142 citation statements)
references
References 3 publications
0
140
0
2
Order By: Relevance
“…In order to analyse the three-dimensional dynamics of vortex rings such as the oval vortex ring and AR4 elliptical vortex ring considered in this study, three-dimensional velocimetry is required. The three-dimensional, threecomponent defocusing digital particle image velocimetry (DDPIV) technique (Willert & Gharib 1992;Pereira & Gharib 2002;Pereira et al 2006) has been applied successfully to non-axisymmetric vortex ring flows by Troolin & Longmire (2009) and Kim & Gharib (2011), and is a promising candidate for performing three-dimensional velocimetry measurements on vortex rigs undergoing large deformations.…”
Section: O'farrell and J O Dabirimentioning
confidence: 99%
“…In order to analyse the three-dimensional dynamics of vortex rings such as the oval vortex ring and AR4 elliptical vortex ring considered in this study, three-dimensional velocimetry is required. The three-dimensional, threecomponent defocusing digital particle image velocimetry (DDPIV) technique (Willert & Gharib 1992;Pereira & Gharib 2002;Pereira et al 2006) has been applied successfully to non-axisymmetric vortex ring flows by Troolin & Longmire (2009) and Kim & Gharib (2011), and is a promising candidate for performing three-dimensional velocimetry measurements on vortex rigs undergoing large deformations.…”
Section: O'farrell and J O Dabirimentioning
confidence: 99%
“…This method was proposed by Willert and Gharib (1992) and applied for macroscopic two phase flow by Pereira et al (2000) and Pereira and Gharib (2002). A theoretical examination of the underlying optics for macroscopic applications was presented by Dabiri (2005, 2008).…”
Section: Defocused Imaging With Aperture (Three-pinhole Technique)mentioning
confidence: 99%
“…Mass et al demonstrated 3d3c measurements with multiple cameras in 1993 [128,129]. The 3d3c tracking with a single camera was introduced by Willert and Gharib in 1992 by using defocussing in connection with a coding aperture that is a mask with three pinholes [130]. As a result, the depth information is extracted from the particle image.…”
Section: Space Measurementmentioning
confidence: 99%